SOLUSI BILANGAN BULAT SUATU PERSAMAAN DIOPHANTINE MELALUI BILANGAN FIBONACCI DAN BILANGAN LUCAS - Bona Martua Siburian; Mashadi '; Sri Gemawati (Jurnal Online Mahasiswa (JOM) Bidang Matematika dan Ilmu Pengetahuan Alam, 2015)
This article discusses the Diophantine equations in the form x 2 + axy + by 2 = c. The values of a, b, and c are constructed by Fibonacci number Fn and Lucas number L n. Furthermore, all integer solutions of the Diophantine equations in the form of Fibonacci number and Lucas number is determined by using Fibonacci and Lucas identities.